Critical coastal dry land-use arming and the Cachapoal valley: planning instruments and territorial management to tackle natural disasters since 2010 to 2019 - Espíndola Vergara, Leandro (Estado, Gobierno y Gestión Pública, 2021)
The present work pretends to contribute to the planning instruments and land-use planning belonging to the coastal non-irrigated land and the intermediate depression regarding aggressive and dynamic natural changes in the O’Higgins region. Those instruments have become obsolete and have low capacity of disaster risk management, especially in the prevention and mitigation phases whose effects provoke damage of the public-private infrastructure, vulnerability, and human losses. Moreover, the socio-natural disasters are a crucial factor that precludes the development of a country for its frequencies, forms, and damaging behaviour along with the local territorial management severity. It produces an asynchrony between the local instruments and national plans to prevent risks. In the end, promoting a preventive cooperation intercommunal model with public-private partnerships, and incorporating the risk factor management approach in the land-planning tools will strengthen vulnerable rural communities.